Photodynamic Physiology—Photonanomanipulations in Cellular Physiology with Protein Photosensitizers - Jiang, Hong Ning; Li, Yuan; Cui, Zong Jie (Frontiers in Physiology, 2017)
Singlet oxygen generated in a type II photodynamic action, due to its limited lifetime (1 μs) and reactive distance (< 10 nm), could regulate live cell function nanoscopically. The genetically-encoded protein photosensitizers (engineered fluorescent proteins such as KillerRed, TagRFP, and flavin-binding proteins such as miniSOG, Pp2FbFPL30M) could be expressed in a cell type- and / or subcellular organelle-specific manner for targeted protein photo-oxidative activation / desensitization. The newly emerged active illumination technique provides an additional level of specificity. Typical examples of photodynamic activation include permanent activation of G protein-coupled receptor CCK1 and photodynamic activation of ionic channel TRPA1. Protein photosensitisers have been used to photodynamically modulate major cellular functions (such as neurotransmitter release and gene transcription) and animal behavior. Protein photosensitisers are increasingly used in photon-driven nanomanipulation in cell physiology research.